Det johannæiske problem - Nielsen, Jesper Tang (Dansk Teologisk Tidsskrift, 2010)
On the basis of Martin Hengel’s work the article discusses the “Johannine question”. I survey the arguments for Hengel’s interpretation and present an alternative hypothesis about the historical setting of the Fourth Gospel. It is proposed that it derives from Alexandria and has later been connected to Ephesus because the author was identified with the author of Revelation. It is further argued that the gospel’s main objective was to explain Jesus’ absence. This question became relevant after the Christological struggles that came to the fore in 1 John. This interpretation is combined with the theory that the beloved disciple is a stereotype which legitimizes John’s presentation of Jesus.